The Influence of Mathematical Logical Intelligence and Spatial Visual Intelligence on the Ability to Interpret Kinematic Graphics - Usman*; Setiawan, Trisno (Physics Education, 2025)
This research aims to describe the influence of mathematical logical intelligence and visual spatial intelligence on the ability to interpret kinematic graphs for class XI MIPA SMA Negeri 5 Makassar, both individually and in groups. This research is ex-post facto research. The research population was all students in class XI MIPA SMA Negeri 5 Makassar totaling 288. The sampling method used was simple random sampling. The technique used to determine the sample size was the Solvin technique at the α = 0.05 level and the sample obtained was 190 people. Measurement of mathematical logical intelligence and visual spatial intelligence with the ability to interpret kinematic graphs using test instruments in the form of multiple-choice questions each with 15 questions and the Test of Understanding Graph – Kinematics version 4.0 with 20 questions. The research data was processed using descriptive statistics, linear regression and product moment correlation. The results of the research reveal that (1) there is a significant influence between logical-mathematical intelligence and the ability to interpret kinematic graphs of class XI MIPA students at SMA Negeri 5 Makassar, (2) there is a significant influence between visual-spatial intelligence and the ability to interpret kinematic graphs of class SMA Negeri 5 Makassar and (3) there is a significant influence of logical-mathematical intelligence and visual-spatial intelligence together on the ability to interpret kinematic graphs of students in class XI MIPA SMA Negeri 5 Makassar.